DEN MAGISKE ILLUSION? En kognitiv tilgang til magiske ritualer - Sørensen, Jesper (Tidsskriftet Antropologi, 2000)
The concept of magic is one of the most contested concepts in anthropology. It has been criticised as an illusion created by early anthropology’s primitivist understanding of other – notably non-European – cultures. This has led to a general agreement to abandon the term, if not in praxis then theoretically. The author questions whether the concept should be abandoned and instead he proposes a reformulation based on the realisation that magic is a broad analytical category about which one cannot produce theories. Rather, theories must address the phenomena observed and categorised as magic. The author advocates a cognitive approach to magic and magical ritual based on the theory of “conceptual blending” proposed by linguist Gilles Fauconnier and literary Mark Turner. The theory of conceptual blending presents a new possibility to approach the explicitly metaphorical and metonymic content in magical practices and spells. Thus, magic is not based on a special type of causality, but rather in the exploitation of ordinary cognitive procedures in special pragmatic circumstances, namely ritual, in order to achieve a specific result. At the same time, the author aims to show how symbolic interpretations are de-emphasised in magical rituals in order to enhance more basic processes of meaning construction, which gives magic a special relation to institutionalised religion.